2021
DOI: 10.1142/s021945542150108x
|View full text |Cite
|
Sign up to set email alerts
|

Using a Single-DOF Test Vehicle to Simultaneously Retrieve the First Few Frequencies and Damping Ratios of the Bridge

Abstract: Bridge damping ratios are extracted via the skillful use of the single-degree-of-freedom (DOF) test vehicle for the first time in this paper. Central to the simultaneous retrieval of the first few frequencies and damping ratios from the contact (point) response of the bridge is the use of the variational mode decomposition (VMD) and random-decrement technique (RDT). Closed-form solutions are newly derived for the vehicle and contact responses of the damped bridge and validated later numerically. Using the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…In this study, it is assumed that the properties of sensing vehicle are known, and vehicle's frequencies are not coincided with those of bridge. Therefore, the bridge related dynamic mono-components can be extracted from vehicle response for the identification of bridge modal frequency and damping ratio (Yang et al, 2021).…”
Section: Bridge Modal Identification Using a Moving Test Vehiclementioning
confidence: 99%
See 1 more Smart Citation
“…In this study, it is assumed that the properties of sensing vehicle are known, and vehicle's frequencies are not coincided with those of bridge. Therefore, the bridge related dynamic mono-components can be extracted from vehicle response for the identification of bridge modal frequency and damping ratio (Yang et al, 2021).…”
Section: Bridge Modal Identification Using a Moving Test Vehiclementioning
confidence: 99%
“…Tian and Zhang (2020) utilized VMD to decompose vehicle-induced bridge responses into IMFs to extract dynamic properties of the VBI coupled system. Yang et al (2021) used VMD to extract the monocomponents from contact-point responses of a VBI model to identify the frequencies and damping ratios of the bridge. The results demonstrated that VMD performed more efficiently and elegantly than EMD/ EEMD in extracting the mono-component responses.…”
Section: Introductionmentioning
confidence: 99%
“…As a first attempt, the dynamic response of a moving test vehicle was used to scan the bridge frequencies of simply supported bridges both theoretically and experimentally. [12][13][14][15][16][17] Furthermore, the vehicle scanning technique has been extended to the extraction of other bridge properties, such as mode shapes, [18][19][20][21][22][23][24][25] damping ratios, 26,27 damages, [28][29][30][31][32] and road surface roughness. [33][34][35] Some up-to-date reviews on applications of the VSM to highway bridges and/or railway tracks are available in Zhu and Law 36 and Yang et al 37 Previously, most researches used the vehicle response, that is, the response recorded by sensors installed on the vehicle's body, to identify the bridge modal properties and damages.…”
Section: Introductionmentioning
confidence: 99%
“…As a first attempt, the dynamic response of a moving test vehicle was used to scan the bridge frequencies of simply supported bridges both theoretically and experimentally 12–17 . Furthermore, the vehicle scanning technique has been extended to the extraction of other bridge properties, such as mode shapes, 18–25 damping ratios, 26,27 damages, 28–32 and road surface roughness 33–35 . Some up‐to‐date reviews on applications of the VSM to highway bridges and/or railway tracks are available in Zhu and Law 36 and Yang et al 37 …”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce vehicle response interference in the signal, the response of the contact point of the vehicle with the bridge, rather than the vehicle itself, is proposed [20]. On this basis, the effect of identifying bridge parameters using the acceleration signals of passing vehicles is further improved, especially the extraction of bridge frequency [21][22][23][24]. The vehicle model is also developed from a single-degree-offreedom (DOF) model to a single-axle vehicle model.…”
Section: Introductionmentioning
confidence: 99%